Strong state and weak minority in post-civil war Sri Lanka: A study based on state-in-society approach - Fowsar, Mohamed Anifa Mohamed; Fazil , Mansoor Mohamed (International research journal of management, IT and social sciences, 2020)
This study aims to analyze the strong state of Sri Lanka that emerged after the civil war during the regime of Mahinda Rajapaksa. The Liberation Tigers of Tamil Eelam (LTTE) was the leading Tamil militant social force, which was waging war against the government to form a separate state in the northern and eastern regions of Sri Lanka. The government ended both the separatist struggle of the LTTE and the civil war in May 2009 by winning a major military victory. This study is a qualitative analysis based on text analysis and field interviews, supplemented with limited observations. The study reveals that the state introduced enhanced security measures to avoid possible LTTE regrouping and re-commencement of violence in the country. The state also attempted to fragment minority parties to weaken the state reconstitution process through penetration and regulation of the social order.